ANALISIS YURIDIS TERHADAP PENOLAKAN PERMOHONAN PRAPERADILAN RAVIO PATRA BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1981 TENTANG HUKUM ACARA PIDANA - Catherina Amanda Putri (Fakultas Hukum Universitas Tarumanagara, 2021)
The competent authority's coercive efforts made in the investigation and prosecution can be controlled through pretrial institutions. The purpose of this institution was formed so that the rights of suspects can be protected, especially in terms of arrest or unlawful detention and termination of investigation or prosecution. Even though the institution has been regulated in positive law, but in its application, there are still weaknesses both in the formulation and in its application in the Court so that there is no protection of rights human rights for the suspect. In practice, it often happens that the submission of a pretrial application by the suspect or his family or the other party on the authority of the suspect regarding the validity of the arrest or detention, before the pretrial examination is completed, becomes invalid because the main criminal case has already begun to be tried. This results in the suspect remaining in custody. At the same time, the possibility that the pretrial will give a decision on the arrest or detention is invalid. This harms the suspect, the image of the law, and justice. Pretrial has expanded its powers. The expansion of the pretrial authority can provide more functions than the pretrial institution itself. Besides the expansion of authority, it is more important to protect the human rights of suspects in the future. The author uses normative legal research methods. With conduct an assessment through library research and secondary data by studying books, journals, internet sites, laws and regulations, doctrines, and other documents related to the object of research. Primary data is data obtained from the results of direct research conducted through interviews.